A low-voltage wide-swing programmable-gain current amplifier - de Lima, J. A. (Kluwer Academic Publ, 2004)
A CMOS low-voltage, wide-swing continuous-time current amplifier is presented. Exhibiting an open-loop architecture, the circuit is composed of transresistance and transconductance stages built upon triode-operating transistors. In addition to an extended dynamic range, the current gain can be programmed within good accuracy by a rapport involving only transistor geometries and tuning biases. Low temperature-drift on gain setting is then expected.In accordance with a 0.35 mum n-well CMOS fabrication process and a single 1.1 V-supply, a balanced current-amplifier is designed for a programmable gain-range of 6 - 34 dB and optimized with respect to dynamic range. Simulated results from PSPICE and Bsim3v3 models indicate, for a 100 muA(pp)-output current, a THD of 0.96 and 1.87% at 1 KHz and 100 KHz, respectively. Input noise is 120 pArootHz @ 10 Hz, with S/N = 63.2 dB @ 1%-THD. At maximum gain, total quiescent consumption is 334 muW. Measurements from a prototyped amplifier reveal a gain-interval of 4.8-33.1 dB and a maximum current swing of 120 muA(pp). The current-amplifier bandwidth is above 1 MHz.
Keywords: low-voltage current amplifier; current-mode design; programmable-gain amplifier; triode-MOSFET circuits